Efficacy of 670 nm Light Therapy to Protect against Photoreceptor Cell Death Is Dependent on the Severity of Damage. (28th February 2016) - Chu-Tan, Joshua A.; Rutar, Matt; Saxena, Kartik; Wu, Yunlu; Howitt, Lauren; Valter, Krisztina; Provis, Jan; Natoli, Riccardo
Abstract : Photobiomodulation at a wavelength of 670 nm has been shown to be effective in preventing photoreceptor cell death in the retina. We treated Sprague-Dawley (SD) rats with varying doses of 670 nm light (9; 18; 36; 90 J/cm 2 ) before exposing them to different intensities of damaging white light (750; 1000; 1500 lux). 670 nm light exhibited a biphasic response in its amelioration of cell death in light-induced degeneration in vivo . Lower light damage intensities required lower doses of 670 nm light to reduce TUNEL cell death. At higher damage intensities, the highest dose of 670 nm light showed protection. In vitro, the Seahorse XFe96 Extracellular Flux Analyzer revealed that 670 nm light directly influences mitochondrial metabolism by increasing the spare respiratory capacity of mitochondria in 661 W photoreceptor-like cells in light damaged conditions. Our findings further support the use of 670 nm light as an effective treatment against retinal degeneration as well as shedding light on the mechanism of protection through the increase of the mitochondrial spare respiratory capacity.